Intravenous Immunoglobulins: Mode of Action and Indications in Autoimmune and Inflammatory Dermatoses - Lyubomir A. Dourmishev; Dimitrina V. Guleva; Ljubka G. Miteva (International Journal of Inflammation)
Intravenous immunoglobulins (IVIGs), a mixture of variable amounts of proteins (albumin, IgG, IgM, IgA, and IgE antibodies), as well as salt, sugar, solvents, and detergents, are successfully used to treat a variety of dermatological disorders. For decades, IVIGs have been administered for treatment of infectious diseases and immune deficiencies, since they contain natural antibodies that represent a first-line defense against pathogens. Today their indication has expanded, including the off-label therapy for a variety of autoimmune and inflammatory diseases. In dermatology, IVIGs are administered for treatment of different disorders at different therapeutic regimens, mostly with higher doses then those administered for treatment of infectious diseases. The aim of this prospective review is to highlight the indications, effectiveness, side effects, and perspectives of the systemic treatment with IVIGs for patients with severe, life-threatening, and resistant to conventional therapies autoimmune or inflammatory dermatoses.